Well‐Defined, Versatile and Recyclable Half‐Sandwich Nickelacarborane Catalyst for Selective Carbene‐Transfer Reactions. Issue 18 (3rd March 2021) - Wang, Linghua; Perveen, Saima; Ouyang, Yizhao; Zhang, Shuai; Jiao, Jiao; He, Gang; Nie, Yong; Li, Pengfei
Abstract: Catalytic carbene‐transfer reactions constitute a class of highly useful transformations in organic synthesis. Although catalysts based on a range of transition‐metals have been reported, the readily accessible nickel(II)‐based complexes have been rarely used. Herein, an air‐stable nickel(II)‐carborane complex is reported as a well‐defined, versatile and recyclable catalyst for selective carbene transfer reactions with low catalyst loading under mild conditions. This catalyst is effective for several types of reactions including diastereoselective cyclopropanation, epoxidation, selective X−H insertions (X = C, N, O, S, Si), particularly for the unprotected substrates. This represents a rare example of carborane ligands in base metal catalysis. Abstract : The readily accessible metal nickel(II) species with a dicarbollide ligand has been introduced as catalyst. The advantages of nickelacarborane as a catalyst for carbene transfer reactions include: 1) air‐stable, versatile, well‐defined, recyclable (at least 5 runs), 2) low catalyst loading, mild conditions, 3) 7 types of reactions in good yield (up to 99 % yield) and selectivity, including diastereoselective cyclopropanation, epoxidation (d.r. > 20:1), chemoselective or site‐selective X−H insertion (X = C, N, O, S, Si), particularly for the unprotected substrates; 4) the uncommon mechanism of nickel(II) acceptor‐containing carbene intermediates.